Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2001
DOI: 10.1016/s0014-5793(01)03174-x
|View full text |Cite
|
Sign up to set email alerts
|

Multiple interactions of the cytosolic polyproline region of the CD95 ligand: hints for the reverse signal transduction capacity of a death factor1

Abstract: The CD95/Fas/Apo-1 ligand is expressed on activated lymphocytes, NK cells, platelets, certain immune-privileged cells and some tumor cells and induces apoptosis through the death receptor CD95/Fas/Apo-1. In murine T cells, membrane-bound CD95L (Fas ligand) also acts as a costimulatory receptor to coordinate activation and function in vivo. The molecular basis for this reverse signal transduction is yet unknown. In the present report, we identify individual interaction domains of enzymes and adapter molecules t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
53
0

Year Published

2003
2003
2010
2010

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 52 publications
(55 citation statements)
references
References 57 publications
2
53
0
Order By: Relevance
“…These include the Src-like kinases Fyn, Lyn, and Fgr and the adaptor proteins Nck, Grb2 and PSTPIP. 28,[35][36][37][38][39] Of interest is the recently described interaction between Nck and FasL, as Nck likely links preformed and granule-stored FasL to WASP and the cytoskeleton. 38 In agreement with our observation that PMA-induced FasL degranulation was latrunculin B-sensitive it was found that the delivery of FasL to the immunological synapse was dependent on actin filament formation.…”
Section: Discussionmentioning
confidence: 99%
“…These include the Src-like kinases Fyn, Lyn, and Fgr and the adaptor proteins Nck, Grb2 and PSTPIP. 28,[35][36][37][38][39] Of interest is the recently described interaction between Nck and FasL, as Nck likely links preformed and granule-stored FasL to WASP and the cytoskeleton. 38 In agreement with our observation that PMA-induced FasL degranulation was latrunculin B-sensitive it was found that the delivery of FasL to the immunological synapse was dependent on actin filament formation.…”
Section: Discussionmentioning
confidence: 99%
“…10 After centrifugation, cell lysates were incubated for at least 90 min. rotating at 4 C with the respective GST fusion protein (20-40 lg) and glutathione sepharose beads (GE Healthcare).…”
Section: (Co)-immunoprecipitationmentioning
confidence: 99%
“…In general, ligand/receptor interactions of members of these families regulate key events in cellular activation, proliferation, differentiation, cell death and survival of immune cells and other tissues. 53 Since most of the TNF family members act as membrane-bound factors and 54 ). Thus, the ligand/ receptor complexes of OX40L/CD134 (TNFSF4/TNFRSF4), CD154/CD40 (TNFSF5/TNFRSF5), CD70/CD27 (TNFSF7/ TNFRSF7), CD153/CD30 (TNFSF8/TNFRSF8), 4-1BB-L/ CD137 (TNFSF9/TNFRSF9), TRANCE/RANK (TNFSF11/ TNFRSF11), LIGHT/LIGHTR (TNFSF14/TNFRSF14) [55][56][57] and the death factors TNF, TRAIL (TNFSF10) 58 and CD95L (TNFSF6) were reported to convey retrograde signals.…”
Section: Cd95l and Other Bidirectional Signal Transducers With Cki Sumentioning
confidence: 99%